Current promising treatment strategy for glioblastoma multiform: A review - Sanjib Bahadur; Arvind Kumar Sahu; Pragya Baghel; Suman Saha (Frontiers Media S.A., 2019)
Glioblastoma multiform (GBM) is a heterogeneous group of primary neoplasm resistant to conventional therapies. Due to their infiltrative nature it not fully isolated by aggressive surgery, radiation and chemotherapy showing poor prognosis in glioma patients. Unfortunately, diagnosed patients die within 1.5-2 year treatment schedule. Currently temozolomide (TMZ) is the first choice for the prognosis of GBM patients. TMZ metabolites methyl triazen imidazol carboxamide form complex with alkyl guanine alkyl transferase (O6 MGMT- DNA repair protein) induced DNA damage following resistance properties of TMZ and inhibit the overall survival of the patients. Last few decades different TMZ conjugated strategy is developed to overcome the resistance and enhance the chemotherapy efficacy. The main aim of this review is to introduce the new promising pharmaceutical candidates that significantly influence the therapeutic response of the TMZ in context of targeted therapy of glioblastoma patients. It is hoped that this proposed strategy are highly effective to overcome the current resistance limitations of TMZ in GBM patients and enhance the survival rate of the patients.